2017
DOI: 10.1038/srep40984
|View full text |Cite
|
Sign up to set email alerts
|

Early Secreted Antigenic Target of 6-kDa of Mycobacterium tuberculosis Stimulates IL-6 Production by Macrophages through Activation of STAT3

Abstract: As early secreted antigenic target of 6 kDa (ESAT-6) of Mycobacterium tuberculosis (Mtb) is an essential virulence factor and macrophages are critical for tuberculosis infection and immunity, we studied ESAT-6 stimulated IL-6 production by macrophages. ESAT-6 stimulated significantly higher IL-6 secretion by murine bone marrow derived macrophages (BMDM) compared to culture filtrate protein 10 kDa (CFP10) and antigen 85A. Polymyxin B, an LPS blocker, did not affect ESAT-6 stimulated macrophage IL-6 production. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 66 publications
(89 reference statements)
3
37
0
1
Order By: Relevance
“…Thus, we speculate that ESAT-6 may function as both priming and activation signals for IL-1β production in tuberculosis infection. As a priming signal, we showed that either incubation of macrophages or intranasal treatment of mouse with ESAT-6 induced pro-IL-1β expression, consistent with our previous reports that ESAT-6 stimulates macrophage production of inflammatory cytokine and chemokine (19, 38). As an activation signal, our data with MCC950, a novel selective NLRP3 inhibitor (23, 24), showed that Mtb stimulates mature IL-1β production by macrophages in an NLRP3 dependent manner, consistent with the previous study [16].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Thus, we speculate that ESAT-6 may function as both priming and activation signals for IL-1β production in tuberculosis infection. As a priming signal, we showed that either incubation of macrophages or intranasal treatment of mouse with ESAT-6 induced pro-IL-1β expression, consistent with our previous reports that ESAT-6 stimulates macrophage production of inflammatory cytokine and chemokine (19, 38). As an activation signal, our data with MCC950, a novel selective NLRP3 inhibitor (23, 24), showed that Mtb stimulates mature IL-1β production by macrophages in an NLRP3 dependent manner, consistent with the previous study [16].…”
Section: Discussionsupporting
confidence: 91%
“…Mouse bone marrow-derived macrophages (BMDMs) were prepared as previously described with minor modifications (19).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In macrophages, ESAT-6-induced IL-6 or IL-10 expression have been identified as possible causes. 52,53 In addition to spontaneous IL-10 and IL-6 production, T-cells from tuberculosis patients were strongly activated in the presence of M. tuberculosis PPD to produce IL-10 and IL-6. These results suggested a dominant immunosuppressive T-cell phenotype in tuberculosis patients characterized by IL-10-positive M. tuberculosis-specific T-cells.…”
Section: Discussionmentioning
confidence: 99%